2023
DOI: 10.1038/s41598-023-28276-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon, total nitrogen stocks and CO2 emissions in top- and subsoils with contrasting management regimes in semi-arid environments

Abstract: This study aims to investigate soil organic carbon (SOC) and total nitrogen (TN) contents and stocks, CO2 emissions and selected soil properties in croplands, grazing lands, exclosures and forest lands of semi-arid Ethiopia. Sampling was done at 0–30, 30–60 and 60–90 cm soil depths and concentration and stocks of SOC, TN and selected soil properties were determined using standard routine laboratory procedures. There were variations in distribution of SOC and TN stock over 90 cm depth across land use types and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The carbon content of soils is a crucial factor in understanding soil fertility, nutrient cycling, and overall soil health. Soil organic carbon (SOC) is vital in soil structure, water-holding capacity, and nutrient availability, influencing plant growth and ecosystem functions [27] [28] [29]. The findings of the study revealed that the type of amendment applied to the soil significantly affects its carbon content.…”
Section: Fertility Index (Fi) and Mineralization Potential Of Compost...mentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon content of soils is a crucial factor in understanding soil fertility, nutrient cycling, and overall soil health. Soil organic carbon (SOC) is vital in soil structure, water-holding capacity, and nutrient availability, influencing plant growth and ecosystem functions [27] [28] [29]. The findings of the study revealed that the type of amendment applied to the soil significantly affects its carbon content.…”
Section: Fertility Index (Fi) and Mineralization Potential Of Compost...mentioning
confidence: 99%
“…Potentially toxic elements in agricultural soil are an exceptional concern for food safety and human health since they can enter the food chain and cause plant and human health hazards [29] [47] [48]. This study analysed the dynamic of PTEs such as As, Cd, Cr, Li, Ni, Hg, and Pb and their bioremediation in the soil due to bio-compost amendment.…”
Section: Clean Index (Ci) and Bioremediation Potential Of Compost Ame...mentioning
confidence: 99%
“…Both under the conditions of self-development and in the course of the reaction of non-environmental influence, the quasi-stable state of Organic Matter (OM) leads to the sequestration of carbon from the atmosphere into soils and bio sediments, which determines the role of soil cover state and stability in the regulation of global carbon balance [3]. About 2344 Gt of Corg are deposited in the soil cover of the world, while its reserves reflect the balance between the decomposition of organic matter and the stabilization of assimilated carbon by soil microorganisms, and this balance can change depending on various biophysical conditions [4].…”
Section: Introductionmentioning
confidence: 99%